Continuous use of intermittent bladder catheterization - can social support contribute? - Marjoyre Anne Lindozo Lopes; Elenice Dias Ribeiro de Paula Lima (Universidade de São Paulo, 2014)
OBJECTIVE: to investigate the factors affecting the adequate continuous use of intermittent catheterization and its relation with social support.METHOD: sectional, descriptive and correlational study involving 49 patients with neuropathic bladder caused by spinal cord injury.RESULTS: almost all (92%) participants continued the intermittent catheterization, but 46.9% made some changes in the technique. The complications (28.6% of the sample) were mainly infection and vesicolithiasis. There were high scores for social support in relation to people that were part of the patient's social support.CONCLUSION: All of them noticed great support from the family, but not from the society in general. The difficulties were related to the lack of equipment and inadequate infrastructure, leading to changes that increased urologic complications.